Enhancing Organizational Success Through a Positive Communication Climate: Concept, Influential Factors, and Practical Approaches - Rahmawati, Milatul; Hayati, Hazimah Dzikra; Syahril, Syahril; Kadri, Hanif Al (Postgraduate School, Universitas Negeri Padang, 2024)
The purpose of this article is to provide readers with a comprehensive understanding of the organizational communication climate. It is hoped that this study will support academics and practitioners in devising strategic organizational communication policies. A critical factor in determining organizational success is the communication climate, which encapsulates members' perceptions of the patterns, quality, and clarity of communication within their workplace. A positive communication climate enhances motivation, job satisfaction, and productivity, while a negative climate hinders the flow of information, provokes conflicts, and diminishes organizational effectiveness. To investigate these dynamics, this study employs a literature review method, focusing on the organizational communication climate's conceptual foundation, influential factors, and impact on organizational performance. The findings indicate that openness, effectiveness, and continuity of communication are pivotal in fostering a supportive work environment. Moreover, elements such as communication skills, social support, and the physical environment significantly contribute to establishing a conducive communication climate. By improving the communication climate, organizations can strengthen members' trust, encourage collaboration, and cultivate commitment to shared goals, thereby promoting the organization’s overall success.